Clinical significance of electrocardiographic markers of myocardial damage prior to aortic valve replacement. (15th May 2020) - Coisne, Augustin; Ninni, Sandro; Pontana, François; Aghezzaf, Samy; Janvier, Florent; Mouton, Stéphanie; Ridon, Hélène; Ortmans, Staniel; Seunes, Claire; Wautier, Marine; Coppin, Amandine; Madika, Anne-Laure; et al.
Abstract: Background: Pre-operative myocardial fibrosis and remodeling impact on outcomes after aortic valve replacement (AVR). We aimed at investigating the prognostic impact of preoperative electrocardiographic (ECG) markers of left ventricular (LV) myocardial damage, i.e. bundle branch block (BBB) and ECG strain pattern after (surgical or transcatheter) AVR for severe aortic stenosis (AS). Methods: Between April 2008 and October 2017, we explored consecutive patients referred to our Heart Valve Clinic for first AVR for severe AS. Detailed pre-operative phenotyping and ECG analysis were performed. Patients were followed-up after AVR for major cardiac events (ME), i.e. cardiovascular death, cardiac hospitalization for acute heart failure and stroke. Results: BBB and ECG strain were respectively observed in 13.5 and 21% of the 1122 patients included. These ECG markers identified a subgroup of older patients, with higher NYHA class and more advanced myocardial disease as detected by echocardiography, i.e. higher LV mass and lower LV ejection fraction, global longitudinal strain and integrated backscatter, than patients without ECG strain or BBB. ME occurred in 212 (18.6%) patients during a mean follow-up of 4.4 ± 1.5 years with higher incidence in case of ECG strain or BBB (HR 1.56, 95%CI 1.13–2.14, p  = 0.006; HR 1.47, 95%CI 1.02–2.13, p  = 0.04 respectively). The prognostic value of ECG strain remained significant after adjustment for age, diabetes and pre-operative LVEF. Conclusions: Pre-operative ECG markers of myocardial damage identify a subgroup of AS patients at high risk of post-AVR cardiovascular complications irrespective of other prognostic factors and should help the multiparametric staging of cardiac damage to guide AVR. Highlights: BBB and ECG strain are markers of myocardial damage. They were observed in a third of a cohort of 1122 patients prior to AVR. They identify a subgroup of patients with more advanced myocardial disease. They were also associated with high risk of post-AVR cardiovascular complications. Thus, they should help the multiparametric staging of cardiac damage to guide AVR.